Memorandum of understanding between Universiti Teknologi MARA and Volgograd State Medical University / Fakulti Perubatan - Universiti Teknologi MARA, Fakulti Perubatan (Universiti Teknologi MARA (UiTM), 2019)
1) Collaboration for research and professional medical development in postgraduate education programmes, medicine and pharmacy 2) Short term advanced professional